The Importance of Weight Change Experiences for Performance of Diabetes Self-Care: A Patient-Centered Approach to Evaluating Clinical Outcomes in Type 2 Diabetes. Issue 4 (December 2015) - Traina, Shana; Slee, April; Woo, Sangsoon; Canovatchel, William
Abstract Introduction The aim of this study was to examine the influence of weight change experiences over time on motivation to perform diabetes self-care behaviors using data from a study of canagliflozin (an agent that inhibits sodium glucose co-transporter 2) versus glimepiride in dual therapy with metformin and background diet/exercise. Methods Weight and motivation for performing healthy behaviors were collected at baseline and over time. The motivation questionnaire enabled categorization into two groups: those performing or not performing health behaviors. Four distinct patterns of weight change were determined: losing weight, gaining weight, and two patterns for fluctuating weight. The relationships between these patterns and motivation for weight loss, following a diet, and exercise were examined using logistic regression models. Results Of 1182 subjects, more than half were already performing behaviors to lose weight, diet, and exercise at baseline. Among those who were not, 52% (246/474) started taking action to lose weight after baseline, 54% (241/448) started following a diet, and 42% (232/556) started exercising. Weight change patterns were significantly related to performance of healthy behaviors at follow-up (week 36). Compared to the weight gain pattern, those who experienced a continuous weight loss pattern from baseline to week 36 were 2.2 (95% confidence interval 1.49, 3.37) times more likely to perform the healthy behaviors. Baseline behavior and confidence were also predictive of performing healthy behaviors. Conclusion The current work highlights the importance of weight change patterns for performance of diabetes self-care. Tracking weight patterns over time, assessing confidence for performance of healthy behaviors, and being aware of the relationship between weight changes and diabetes self-care behaviors are viable, concrete ways to practice patient-centered care. Funding Janssen Global Services, LLC.